2013
DOI: 10.1111/jce.12084
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Total Atrial Conduction Time Estimated via Tissue Doppler Imaging (PA‐TDI Interval), Structural Atrial Remodeling and New‐Onset of Atrial Fibrillation After Cardiac Surgery

Abstract: PA-TDI interval is useful to identify patients at risk for POAF undergoing cardiac surgery and correlates with the degree of atrial fibrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
66
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 50 publications
(70 citation statements)
references
References 25 publications
(41 reference statements)
3
66
0
1
Order By: Relevance
“…Previously, our working group showed significant correlation of Fas-Ligand, an apoptosis biomarker, to atrial histological remodeling in patients undergoing cardiac surgery [26].…”
Section: Cardiac Biomarkers and Potential Clinical Implicationsmentioning
confidence: 99%
“…Previously, our working group showed significant correlation of Fas-Ligand, an apoptosis biomarker, to atrial histological remodeling in patients undergoing cardiac surgery [26].…”
Section: Cardiac Biomarkers and Potential Clinical Implicationsmentioning
confidence: 99%
“…This cohort covers a subset of the population of a previous trial that evaluated the prognostic value of TACT for the onset of POAF [24]. After approval by the local institutional ethics committee on human study of the Ruhr University of Bochum (Bochum, Germany) we prospectively enrolled 39 noncritically ill patients who underwent cardiac surgery (coronary artery bypass graft, CABG, and/or aortic valve replacement, AVR).…”
Section: Methodsmentioning
confidence: 99%
“…In addition to surgery-associated factors (like inflammation, oxidative stress and increased sympathetic drive), preexisting factors, including ion channel alterations, interstitial impairments, myocardial apoptosis and fibrosis, may provide pathophysiological substrates of POAF [19,23,24]. …”
Section: Introductionmentioning
confidence: 99%
“…PA-TDI interval, an echocardiographic parameter that combines electrical and mechanical information in order to derive a total atrial conduction time, is an independent predictor of new-onset AF and recurrent AF after catheter ablation and eCV [4,7,11,[14][15][16][17]. Recently, we showed that the PA-TDI interval predicts early recurrent atrial fibrillation (within 7 days) after successful eCV and moreover reflects the extent of structural atrial remodeling in patients undergoing cardiac surgery [4,7].…”
Section: Introductionmentioning
confidence: 99%
“…Electrical cardioversion (eCV) has been proven to be an effective treatment option aimed at the acute restoration of sinus rhythm (SR) [2], but recurrence rates without the use of additional anti-arrhythmic drug (AAD) therapy in the first weeks is high [3,4]. AF is related to left atrial fibrosis, the hallmark of structural atrial remodeling [5][6][7][8][9]. Electrical and structural atrial remodeling has been found to be independently associated with a higher recurrence rate of AF after eCV or catheter ablation [4,[9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%